2015
DOI: 10.1186/s12889-015-1625-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of a rights-based sexuality education curriculum for high-school students: a cluster-randomized trial

Abstract: BackgroundAn emerging model for sexuality education is the rights-based approach, which unifies discussions of sexuality, gender norms, and sexual rights to promote the healthy sexual development of adolescents. A rigorous evaluation of a rights-based intervention for a broad population of adolescents in the U.S. has not previously been published. This paper evaluates the immediate effects of the Sexuality Education Initiative (SEI) on hypothesized psychosocial determinants of sexual behavior.MethodsA cluster-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 49 publications
1
56
0
3
Order By: Relevance
“…40,41 In India, in particular, it is important to consider how to ensure that unmarried women, especially those who are young, are aware of their right to care and informed about how to access safe and legal abortion services. Comprehensive sexuality education has been found to inform young people about sexual health services and promote care-seeking behaviour in various contexts, [41][42][43] and could be explored as a strategy to inform younger and unmarried women about their right to abortion care and how to access it.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 In India, in particular, it is important to consider how to ensure that unmarried women, especially those who are young, are aware of their right to care and informed about how to access safe and legal abortion services. Comprehensive sexuality education has been found to inform young people about sexual health services and promote care-seeking behaviour in various contexts, [41][42][43] and could be explored as a strategy to inform younger and unmarried women about their right to abortion care and how to access it.…”
Section: Discussionmentioning
confidence: 99%
“…Após definidos e estudados os temas abordados pelo projeto e experiências de educação sexual em escolas (SOUZA et al 2007, CONSTANTINE et al 2015, PAIVA et al 2004, AYRES et al 2003, AYRES, 2002, foram elaboradas propostas de oficinas, identificando tópicos prioritários e modos de abordá-los. Resumidamente, a oficina de HIV incluiu: a diferenciação entre infecção por HIV e AIDS; a epidemiologia da infecção; conceitos de grupo e comportamento de risco e de vulnerabilidade; estigma do portador do HIV; modos de contágio e prevenção; como se testar; e tratamento.…”
Section: Métodosunclassified
“…One paper reported on the development of a sexuality education initiative (SEI), involving 8 independent charter schools in Los Angeles. A cluster‐randomized trial evaluation found that, at immediate post‐test, the SEI improved students' sex‐ and sexuality‐related knowledge, attitudes, communication, and self‐efficacy . One year later, SEI participants had higher sexual health knowledge, partner communication, protection self‐efficacy, access to health information, and awareness of sexual health services, compared with control youth .…”
Section: Implications For School Healthmentioning
confidence: 99%